Visualization in engineering - Curtin University; Dongbei da xue (1993); Guo li Taiwan da xue (Springer-Verlag, GmbH, 2013)
"The aim of Visualization in Engineering is to disseminate original and high quality research results on the visualization paradigms, models, technologies, and applications that have significant contributions to the advancement of all aspects of design and engineering. The journal is devoted to scholarly research on improving all aspects of design and engineering (including civil, mechanical, manufacturing, industrial, aerospace, etc.) through the applications of visualization technologies."
Keywords: Engineering : Research : Periodicals; Visualization : Periodicals; Engineering design : Periodicals; Engineering design; Engineering : Research; Visualization; Engineering - General